2017
DOI: 10.1016/j.scitotenv.2017.07.187
|View full text |Cite
|
Sign up to set email alerts
|

Removal of phenanthrene from coastal waters by green tide algae Ulva prolifera

Abstract: Ulva prolifera (U. prolifera) has been frequently involved in terrible algal proliferation in coastal areas. Although it is known to be associated with green tide, its contribution to the natural attenuation of the polycyclic aromatic hydrocarbons (PAHs) in seawater has not been evaluated. In this study, the removal of phenanthrene using U. prolifera collected from coastal water with green tide blooming was investigated. The results showed that phenanthrene could be removed efficiently in the presence of both … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 43 publications
0
10
0
Order By: Relevance
“…Collectively, these data, demonstrated that P. stutzeri strains isolated from contaminated environments were likely to conserve more pollutant degradation genes, while strain SI-3, a potential endophytic bacterium of U. prolifera , lost the majority of genes involved in aromatic compounds degradation. Interestingly, Zhang et al ( 2017 ) demonstrated that sterilized host U. prolifera was capable of efficiently removing polycyclic aromatic hydrocarbons. In contrast, enrichment of aromatic compounds biodegradation pathways was found in the rhizoplane microbiome by metagenomic sequencing of root microbes of foxtail millet (Jin et al, 2017 ).…”
Section: Resultsmentioning
confidence: 99%
“…Collectively, these data, demonstrated that P. stutzeri strains isolated from contaminated environments were likely to conserve more pollutant degradation genes, while strain SI-3, a potential endophytic bacterium of U. prolifera , lost the majority of genes involved in aromatic compounds degradation. Interestingly, Zhang et al ( 2017 ) demonstrated that sterilized host U. prolifera was capable of efficiently removing polycyclic aromatic hydrocarbons. In contrast, enrichment of aromatic compounds biodegradation pathways was found in the rhizoplane microbiome by metagenomic sequencing of root microbes of foxtail millet (Jin et al, 2017 ).…”
Section: Resultsmentioning
confidence: 99%
“…SMN03 Cefdinir Wastewater was collected from a pharmaceutical industry located in Ranipet, Vellore Dist., India Cefdinir was utilized as a sole carbon source six novel intermediates formed isolate was found to degrade 81% of cefdinir within 6 days and an initial cefdinir concentration of 200 mg/L UV–vis LC-MS FTIR ( Selvi et al., 2014 ) Ochrobactrum sp. Strain WX-J1 Erythromycin A(EA) Soil contaminated by EA was collected at a site near a pharmaceutical factory, Henan, China Strain WX-J1 can utilized EA as a sole source of carbon and energy 3-depyranosyloxy erythromycin A, 7,12-dyhydroxy-6-deoxyerythronolide B, 6-deoxyerythronolide B and propionaldehyde when the initial Erythromycin A concentration was 100 mg/L, 97% of Erythromycin A was degraded HPLC–(UV)-MS ( C. Zhang et al., 2017 ) Citrobacter amalonaticusRashtia Paclitaxel samples were collected from wastewater chamber of the Sobhan oncology pharmaceutical company The isolate utilized Paclitaxel as the sole carbon source. Aerobic degradation pathway is suggested by authors 87–93% efficacy under aerobic condition HPLC ( Zamani et al., 2016 ) …”
Section: Explosive Wastementioning
confidence: 99%
“…JPN2 pyrene crude oil was collected from Dagang Oilfield, Tianjin Province, Northern China Aerobic degradation through dioxygenase enzyme system 4,5-dihydroxy-4,5-dihydropyrene, 4-phenanthrol, 1‑hydroxy-2-naphthoic acid and phthalate 82.88% after 25 d GC–MS ( Jin et al., 2016 ) Pseudomonas sp. JP1 benzo[ a ]pyrene (BaP), fluoranthene, and phenanthrene Shantou Bay, Shantou, China Anaerobic biodegradation with nitrate as the electron acceptor variable 30, 47, and 5%, respectively GC/MS ( Liang et al., 2014 ) Ulva prolifera Phenanthrene coastal water (Rushan City, China) 91.3% ( C. Zhang et al., 2017 ) Chlorella vulgaris fluorene Culture Collection of Algae of Bushehr Shrimp Research Institute, Iran dioxygenase enzyme system based degradation N-Hydroxymethylcarbazol, Dibutyl phthalate, Hexadecanoic acid, ethyl ester, 1,2-Benzenedicarboxylic acid, dioctyl ester GC–MS (Asghari et al., 2019) Anabaena fertilissima anthracene (ant) and pyrene (pyr) center for conservation and utilization of blue green algae, iari, new delhi, india degraded product for ANT was 2, 4-Dimethyl-1-heptene and for PYR it was 2, 3, 4-Trimethylhexane degradation of ANT by 46% and PYR by 33%, at 5.0 mg/L and 3.0 mg/L GC/MS ( Patel et al., 2016 ) Cellulosimicrobium cellulans CWS2 benzo(a)pyrene PAH contaminated soil Anaerobic degradation under nitrate-reducing conditions pyrene, 1-aminopyrene, phenanthrene, 1-methylphenanthrene, 1,7-dimethylnaphthalene, 1-(2-hydroxypropyl)naphthalene, 1-methylnaphthalene, 2‑hydroxy-3-(3-methyl-2-butenyl)−1,4-naphthalenedione, diethyl phthalate, and 2-acetyl-3-methoxybenzoc acid 78.8%) was observed in 13 days GC–MS ( Qin et al., 2018 ) Achromobacter xylosoxidans Strain DN002 Fluoranthene petroleum-contaminated soil Aerobic degradation through dioxygenases (catechol 1,2 d...…”
Section: Pahsmentioning
confidence: 99%
“…It has been pointed out that dead biomass of the algae might be more effective than living ones for the removal of toxic pollutants (Luo et al, 2014). The potential influence of the algal detritus on PAHs existing in aquatic ecosystems with low concentrations is poorly understood although algae serve as the primary producers in coastal and estuarine systems to play an important role in the fate of PAHs in these ecosystems (Zhang et al, 2017a).…”
Section: G R a P H I C A L Abstractmentioning
confidence: 99%